2021
DOI: 10.1016/j.ijbiomac.2020.10.237
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-catalyzed cross-linking of BSA mediated by tyrosine

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
1
9
0
1
Order By: Relevance
“…43 Additionally, a laccase, Laccase1, was identified, which catalyzes the oxidation and crosslinking of phenolic compounds. 38 Thus, tyrosinases, laccases, and other phenoloxidases may increase snail mucus integrity by crosslinking phenols of proteins and metabolites, similar to mechanisms used in other mollusks. 44 No proteins strongly identifying with P. viridis mussel foot glue proteins were identified in this study, though Fibrillin1 and Fibrillin2 showed some sequence similarity to mussel foot proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Additionally, a laccase, Laccase1, was identified, which catalyzes the oxidation and crosslinking of phenolic compounds. 38 Thus, tyrosinases, laccases, and other phenoloxidases may increase snail mucus integrity by crosslinking phenols of proteins and metabolites, similar to mechanisms used in other mollusks. 44 No proteins strongly identifying with P. viridis mussel foot glue proteins were identified in this study, though Fibrillin1 and Fibrillin2 showed some sequence similarity to mussel foot proteins.…”
Section: Resultsmentioning
confidence: 99%
“…29 Several enzymes that were found are involved in protein crosslinking, mucus network formation, or constructing biological glues, and likely serve a similar role in C. aspersum mucus. 38,39 Cysteines are abundant in mucins, and disulfide isomerases, like the identified DisulfideIsomerase1, construct mucus gels by catalyzing interchain disulfide bonds. 39 A prolyl isomerase, ProlylIsomerase1, was found, which has signaling and immune functions in mucus, 40 and this class of proteins also regulates collagen crosslinking.…”
Section: Characterization Of Adhesive Lubricating and Protective C As...mentioning
confidence: 99%
“…The combination of these two protein fragments amounted to the molecular weight of BSA (66 445 Da) and a molecule of water, indicating that cleavage occurs at specific site in BSA by hydrolysis of the protein. An additional peak was also detected in the BSA spectrum, which is corresponding to the protein BSA charged with two H + [20] . However, as the irradiation time extended from 15 min to 30 min, additional protein bands were observed due to the nonspecific shear of the initial protein BSA and the newly generated protein fragments (Supporting Information, Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…An additional peak was also detected in the BSA spectrum, which is corresponding to the protein BSA charged with two H + . [20] However, as the irradiation time extended from 15 min to 30 min, additional protein bands were observed due to the nonspecific shear of the initial protein BSA and the newly generated protein fragments (Supporting Information, Figure S6). Moreover, the change in fluorescence intensity was tested along with the last of the irradiation time and the result obtained through the fitting curve indicated that the time point for the fastest fluorescence attenuation occurs at approximately 12.13 minutes (Supporting Information, Figure S7).…”
Section: Methodsmentioning
confidence: 99%
“…Do badań wybrano białko albuminy surowicy bydlęcej BSA (ang. Bovine Serum Albumin), które jest powszechnie stosowane w warstwach receptorowych biosensorów podczas sieciowania [16] oraz jego kompleksy BSA-Au, BSA-NAA.…”
Section: Badania Wpływu Promieniowania Elektromagnetycznego Na Kompon...unclassified